Optical and color rendering long-term performance of monolithic aerogel after laboratory accelerated aging: Development of a method and preliminary experimental results. (15th March 2023) - Fiorini, Costanza V.; Merli, Francesca; Belloni, Elisa; Anderson, Ann M.; Carroll, Mary K.; Buratti, Cinzia
Highlights: An accelerated aging methodology under temperature and radiation effects was developed. Thermogravimetric analysis allowed the determination of activation energy. After 2.6 years of service life, monolithic hydrophilic aerogel transmission properties are not changed. Aging implies a yellowish hue continuing to give bluish tendency to objects seen through it. Monolithic aerogel ensures a high color rendering performance over the years. Abstract: Innovative transparent solutions such as monolithic aerogel in the building envelope have a considerable impact on both the indoor environmental quality and thermo-acoustic performance. However, the long-term effect of this new material is not yet known in the scientific literature. In this context, the present study investigates the influence of accelerated aging on the optical and color rendering properties of monolithic aerogel. In the aging process, the combined effect of temperature and solar radiation was considered. An acceleration factor for temperature equal to 13.6 was obtained following the Arrhenius Law, after evaluating the activation energy value by means of thermogravimetric analysis. The acceleration factor for radiation was evaluated as the ratio between artificial radiation of the chosen lamps used in the laboratory aging device and the natural radiation of the solar spectrum, by adding the direct and diffuse components related to the site. Accelerated aging equivalent to 2.6 years did not lead to significant changes in the optical transmission properties of the monolithic aerogel; however, the material tends to yellow and a bluish hue is obtained for the color patches seen through the aged material. Furthermore, an increase in the color shift is measured for all colors (from the 5.62–43.40 range to the 6.42–45.30 range), with the higher variations between before and after aging registered for a sample of bluish green color.